2022
DOI: 10.3390/app121910039
|View full text |Cite
|
Sign up to set email alerts
|

Employing Discrete Solid Phases to Represent C-S-H Solid Solutions in the Cemdata07 Thermodynamic Database to Model Cement Hydration Using the PHREEQC Geochemical Software

Abstract: This paper presents a cement hydration model over time using the cemdata07 thermodynamic database and a series of derived discrete solid phases (DSPs) to represent calcium silicate hydrate (C-S-H) as a binary solid solution with two end-members. C-S-H in cement is amorphous and poorly crystalline with a range of molar Ca/Si ratios from 0.6 to 1.7. It displays strongly incongruent dissolution behaviour, where the release of calcium into solution is several orders of magnitude greater than silicon. It is, theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…The CEM I cement has ~2.9% limestone powder content by mass, compared to ~11.23% in the CEM II/A-L, which are both within the limits of EN197-1 [22]. Thermodynamic modelling was performed using PHREEQC [23] using input data to describe the normative clinker content, its dissolution rate, and accounting for minor constituents, oversaturation and alkalis binding to the C-S-H [24][25][26]. Anhydrite (CaSO 4 ) is used here as gypsum.…”
Section: Opc Clinker Rate Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CEM I cement has ~2.9% limestone powder content by mass, compared to ~11.23% in the CEM II/A-L, which are both within the limits of EN197-1 [22]. Thermodynamic modelling was performed using PHREEQC [23] using input data to describe the normative clinker content, its dissolution rate, and accounting for minor constituents, oversaturation and alkalis binding to the C-S-H [24][25][26]. Anhydrite (CaSO 4 ) is used here as gypsum.…”
Section: Opc Clinker Rate Equationsmentioning
confidence: 99%
“…Previous work by Holmes et al [26] has demonstrated how the C-S-H gel phase can be modelled as a series of discrete solid phases (DSPs) using suitable end members in the cemdata18 database. Dissolution reactions and solubility products for the DSP for the CSH-3T model can be calculated on a spreadsheet and suitably formatted such that the user simply needs to copy and paste directly into PHREEQC.…”
Section: C-s-h Gelmentioning
confidence: 99%
“…The thermodynamic modelling was undertaken using the PHREEQC geochemistry software [7] which, using appropriate input for the normative cement content, calculating the clinker dissolution rate while accounting for accessory phases, oversaturation and alkalis binding to the C-S-H, determines the equilibrium phase assemblages over time, as described in detail in [5,6,19,20]. Anhydrite (CaSO 4 ) is referred to here as gypsum.…”
Section: Thermodynamic Modelling Of Cement Hydrationmentioning
confidence: 99%
“…Holmes et al [20] showed how C-S-H gel solubility can be modelled as a series of discrete solid phases (DSPs) derived from the CSH3T and CSHQ end-members in the cemdata18 database. It was shown that for OPC hydration, solid solution models are not required, which only requires portlandite and a suitable C-S-H gel phase of fixed Ca:Si and H (water):Si molar ratio of between 1.6-1.8 and 2.0-2.1, respectively.…”
Section: C-s-h Gelmentioning
confidence: 99%
See 1 more Smart Citation